ANALISIS DETERMINAN LAMA MENGANGGUR TENAGA KERJA TERDIDIK DI KABUPATEN BADUNG PADA MASA PANDEMI COVID-19 - Sanjaya, I Made Haris; Marhaeni, A. A. I. N (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.06.TAHUN.2023DO - 10.24843/EEB.2023.v12.i06.p03, 2023)
The study aims to; 1) analyze the simultaneous effect of marital status, gender, social network, and socioeconomic status of parents on the duration of unemployment of educated; 2) analyze the partial effect of marital status, gender, social network, and socioeconomic status of parents on the duration of unemployment of educated; 3) analyze the socioeconomic status of parents in moderating the influence of social networks on the duration of unemployment of educated. The population in this study is an educated workforce who found work during the Covid-19 pandemic in Badung Regency. The analytical technique used in this study is moderated regression analysis. The results of this study indicate; 1) marital status, gender, social network, and socioeconomic status of parents simultaneously influence the duration of unemployment of educated; 2) educated workers who are married have a tendency to be unemployed for a shorter time than educated workers who are not; 3) male educated workers tend to be unemployed for a shorter time than female educated workers; 4) social network and socioeconomic status of parents have a negative and significant effect on the duration of unemployment of educated; 5) socioeconomic status of parents moderates the influence of social networks on the duration of unemployment of educated workers.